Energy economics : understanding energy security in China - Wei, Yi-Ming; Liang, Qiao-Mei; Wu, Gang; Liao, Hua (Emerald Publishing Limited, 2019)
As the largest energy consuming country and the second largest oil importing country, China has been the net importer of all fossil energy since 2009. With its increasing external energy dependence year by year, as well as frequent occurrences of oil, coal, and electricity shortages, the issue of energy security has been increasingly serious. What is the level of energy security in China? How might we improve national energy supply security and reduce energy trade risks? This book sets out a systematic piece of research which attempts to tackle these hot issues. It starts with the history of world energy geopolitics and domestic energy security, focusing on the hot issues of the complexity of the international energy market, and moves to domestic energy import trade risks, domestic strategic energy reserve strategies, and the impact of the energy crisis on domestic economy. Further insights include the environmental and health effects of energy consumption, the development potential of renewable energy, energy security early-warning and contingency plans, and an international comparison of energy security. The book will be an insightful resource for researchers and students of energy economics and energy management. It will also be a helpful support and reference tool for decision-makers in the energy industry.